Current Understanding of Mycobacterium tuberculosis Drug Resistances and Diagnostics in Indonesia: A Review - Rahayu, Ayu; Rovik, Anwar; Turnip, Oktaviani Naulita (Journal of Experimental and Clinical Pharmacy (JECP), 2024)
Tuberculosis is a significant global infectious disease cause of mortality, with 25% of the world's population caused by Mycobacterium tuberculosis (Mtb). The highest case recorded was 821,200 cases in 2023 over one decade. Drug resistance significantly impacts tuberculosis treatment and has been observed since the first drug discovery, streptomycin. In Indonesia, drug-resistant tuberculosis (DR-TB) is a significant public health issue, with an estimated 24,666 cases recorded in 2022. A comparative literature search was conducted using various articles, including research studies, guidelines, narrative reviews, reports, and meta-analyses, with the inclusion criteria for reference sources including ten years of published articles. Drug resistance in TB can reduce treatment success rate and increase therapy duration. In the result, several general mechanisms proposed for drug resistance in Mtb include efflux pump, enzyme inactivation, permeability barrier, mutations in drug-target genes, and epigenetics. Currently, TB treatment in Indonesia involves combination therapy using three or more types of drugs, such as rifampicin and isoniazid. The International Standard for TB Care (ISTC) serves as the basis for TB diagnosis in Indonesia, which involves a combination of clinical and laboratory tests. Early diagnosis and universal access to the Drug Susceptibility Test (DST) are crucial for TB resistance. In Indonesia, several diagnostic methods, such as sequencing, PCR testing, Gene Xpert, and culture, can be used to identify TB resistance. Understanding the mechanisms of drug resistance and developing effective diagnosis strategies for TB resistance is crucial for managing global infection.